From Khalifah to Consumer: Reconciling Islamic Principles of Environmental Sustainability with Modern Consumption Patterns - Ahmed Shah; Sara Hussain; Fatima Malik (Islamic Studies in the World, 2025)
Contemporary environmental degradation has intensified debates on how Islamic teachings on stewardship align or conflict with modern consumption patterns in Muslim-majority societies. Although the Qur’anic concept of khalifah positions humans as responsible caretakers of the earth, everyday consumer practices often reflect excess, materialism, and resource exploitation—revealing a gap between normative Islamic ethics and lived behaviors. This tension raises important questions regarding how Islamic environmental principles are interpreted, negotiated, and applied within modern consumer cultures. The study aims to analyze the extent to which Islamic principles of environmental sustainability—such as moderation (wasatiyyah), avoidance of waste (israf), and ecological stewardship—can be reconciled with prevailing consumption patterns influenced by globalization, digital markets, and lifestyle aspirations. The research also seeks to identify the cognitive, theological, and socio-cultural factors shaping Muslims’ ecological attitudes. A qualitative approach was employed using semi-structured interviews with Islamic scholars, educators, and urban Muslim consumers in Indonesia, complemented by textual analysis of classical and contemporary Islamic literature on environmental ethics. Thematic analysis was conducted to compare doctrinal ideals with empirical consumer behaviors. Findings reveal a strong theoretical foundation for sustainable living within Islamic teachings, yet significant inconsistencies remain between religious norms and actual consumer practices. Participants acknowledged environmental responsibilities but felt constrained by social expectations, market pressures, and limited institutional guidance. The study concludes that reconciling Islamic environmental ethics with modern consumption requires strengthening eco-theological literacy, promoting structural incentives for sustainable choices, and reinterpreting religious teachings in ways that resonate with contemporary lifestyles.